2017
DOI: 10.1371/journal.pone.0171824
|View full text |Cite|
|
Sign up to set email alerts
|

A novel intraperitoneal metastatic xenograft mouse model for survival outcome assessment of esophageal adenocarcinoma

Abstract: Esophageal adenocarcinoma (EAC) has become the dominant type of esophageal cancer in United States. The 5-year survival rate of EAC is below 20% and most patients present with locally advanced or widespread metastatic disease, where current treatment is largely ineffective. Therefore, new therapeutic approaches are urgently needed. Improvement of EAC patient outcome requires well-characterized animal models in which to evaluate novel therapeutics. In this study we aimed to establish a peritoneal dissemination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 39 publications
(32 reference statements)
2
20
0
Order By: Relevance
“…WST-1 in vitro colorimetric cell proliferation assay revealed that single agent treatment of nab-paclitaxel is more effective in inhibiting both OE19 and OE33 human EAC cancer cell proliferation than PT. We found that OE33 cells are more sensitive to the antiproliferative effect of the anticancer drug treatments we used including nab-paclitaxel than OE19 cells, supporting the more aggressive phenotype of OE19 as we mentioned previously [30] . In addition, nab paclitaxel combination with CP showed stronger inhibition of cell proliferation compared to that of PT combination with CP.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…WST-1 in vitro colorimetric cell proliferation assay revealed that single agent treatment of nab-paclitaxel is more effective in inhibiting both OE19 and OE33 human EAC cancer cell proliferation than PT. We found that OE33 cells are more sensitive to the antiproliferative effect of the anticancer drug treatments we used including nab-paclitaxel than OE19 cells, supporting the more aggressive phenotype of OE19 as we mentioned previously [30] . In addition, nab paclitaxel combination with CP showed stronger inhibition of cell proliferation compared to that of PT combination with CP.…”
Section: Discussionsupporting
confidence: 88%
“…We evaluated the impact of drug treatments on the survival of mice harboring OE19 and OE33 peritoneal disseminated xenograft tumors as described earlier by us [30] . Kaplan-Meier curves of different treatment groups and the comparison are shown in Figure 6 A (OE19) and Figure 6 B (OE33).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations